Inside Back Cover: A DNA Barcode‐Based Aptasensor Enables Rapid Testing of Porcine Epidemic Diarrhea Viruses in Swine Saliva Using Electrochemical Readout (Angew. Chem. Int. Ed. 31/2022). Issue 31 (7th July 2022) - Victorious, Amanda; Zhang, Zijie; Chang, Dingran; Maclachlan, Roderick; Pandey, Richa; Xia, Jianrun; Gu, Jimmy; Hoare, Todd; Soleymani, Leyla; Li, Yingfu
Abstract : Rapid and reagent‐free pathogen tests are urgently needed. In their Research Article (e202204252 ), Leyla Soleymani, Yingfu Li and co‐workers developed a dual‐electrode electrochemical chip (DEE‐Chip) and a barcode‐releasing electroactive aptamer for rapid on‐farm detection of porcine epidemic diarrhea viruses (PEDv). In contrast to current biosecurity surveillance with turnaround times of 2–4 days, this technology identifies infection with PEDv in pig saliva in one hour with a diagnostic sensitivity of 100 % and specificity of 83 %.